2016
DOI: 10.18632/oncotarget.9336
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-RMRP promotes carcinogenesis by acting as a miR-206 sponge and is used as a novel biomarker for gastric cancer

Abstract: Long noncoding RNAs (lncRNAs) play crucial roles in tumorigenesis. However, the mechanisms of most lncRNAs in cancers are largely unknown. Because the RNA component of mitochondrial RNA processing endoribonuclease (RMRP) is one of the dysregulated lncRNAs in gastric cancer, this study explored its molecular mechanisms in carcinogenesis. RMRP levels in 792 tissues, plasma and gastric juices from patients with various stages of gastric tumorigenesis were analyzed by quantitative reverse transcription-polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
136
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 39 publications
6
136
0
Order By: Relevance
“…Previous study showed that RMRP increased aggressive gastric cancer by regulating Cyclin D2 as the ceRNA for miR-206 [31]. In line with this, we demonstrated that overexpression of RMRP suppressed miR-206 expression in lung adenocarcinoma cell.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous study showed that RMRP increased aggressive gastric cancer by regulating Cyclin D2 as the ceRNA for miR-206 [31]. In line with this, we demonstrated that overexpression of RMRP suppressed miR-206 expression in lung adenocarcinoma cell.…”
Section: Discussionsupporting
confidence: 89%
“…Previous study showed that the expression of RMRP was deregulated in gastric cancer [30]. Moreover, Shao et al [31]. showed that RMRP expression level was downregulated in gastric cancer tissues and gastric dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, small non-coding RNAs, such as miRNAs, have been extensively studied, and their roles in gene regulation and cell function have been elucidated in numerous cancers [23-27]. Recent studies have indicated that lncRNA also participate in several different biologic processes and play oncogenic or tumor suppressive roles during tumorigenesis [28-30]. However, the roles of lncRNAs in NSCLC remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 modulates TGF-β1-induced endothelial-to-mesenchymal transition (EndMT) of endothelial progenitor cells through regulation of TGFBR2 and SMAD3 via miR-145 [17]. RMRP promotes carcinogenesis and serves as a novel biomarker for gastric cancer [18]. RP11-708H21.4 is down-regulated in colorectal cancer (CRC) samples, while its upregulation blocked AKT/mTOR pathway and repressed in vivo CRC xenograft tumor growth [19].…”
Section: Introductionmentioning
confidence: 99%